5(p-1)=p+5

Simple and best practice solution for 5(p-1)=p+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(p-1)=p+5 equation:


Simplifying
5(p + -1) = p + 5

Reorder the terms:
5(-1 + p) = p + 5
(-1 * 5 + p * 5) = p + 5
(-5 + 5p) = p + 5

Reorder the terms:
-5 + 5p = 5 + p

Solving
-5 + 5p = 5 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-5 + 5p + -1p = 5 + p + -1p

Combine like terms: 5p + -1p = 4p
-5 + 4p = 5 + p + -1p

Combine like terms: p + -1p = 0
-5 + 4p = 5 + 0
-5 + 4p = 5

Add '5' to each side of the equation.
-5 + 5 + 4p = 5 + 5

Combine like terms: -5 + 5 = 0
0 + 4p = 5 + 5
4p = 5 + 5

Combine like terms: 5 + 5 = 10
4p = 10

Divide each side by '4'.
p = 2.5

Simplifying
p = 2.5

See similar equations:

| 5/8÷25/16= | | 2-4x=3x-5 | | e(2x+1)+7e(x)-15=0 | | 7x=31412+312 | | 36t^2+128t^3=9 | | -36t^2+128t^3=9 | | 5+3=x-3x-2x | | -72*t^2+256*t^3=18 | | x^10=1.55 | | x^10=15 | | 140x+x=180 | | -4x^3=-4x | | -2+a-b+1=0 | | 1+a+2b+4=0 | | x+4*3-4=65 | | (x-9)(x-12)=0 | | a=bx+cx^3 | | 7x-2y+4=o | | 2x-8x+13=26-x+14 | | 4-4x=4x+4 | | 3a+3b-2ab=0 | | 16-3x=11-21x | | 8-6x=9+x | | 13+7x=6-7x | | 8(3x-8x)(4x+9)=0 | | 14x-9=5x | | 17x-3=3x+11 | | 14x-9x=5x | | 29x=9+2x | | 9m-12=160 | | 15v=-8v | | x^3+8x^2+17x-4=0 |

Equations solver categories